Valoración de recursos frutales aplicando NIC 41 en la asociación de producción agropecuaria Ecuabija puntal - Escobar Casanova, Hugo Xavier (2025)
The study analyzed the application of International Accounting Standard (IAS) 41 in the valuation of biological assets in the Ecuabija Puntal Agricultural Production Association (Asociación de Producción Agropecuaria Ecuabija Puntal), made up of small and medium-sized apple growers, with emphasis on the Anna variety. This variety, recently introduced in Ecuador, showed good production results with harvests between February and July. The implementation of IAS 41 was evaluated to address the challenges related to the correct valuation of biological assets in the context of agricultural accounting. A mixed approach, combining quantitative and qualitative methods, was used to analyze the interpretation and application of the standard by key stakeholders. Key accounting entries considered included land acquisition, planting and production costs, as well as the revaluation of biological assets. The results showed that the adoption of IAS 41 improved the accuracy of accounting records, which facilitated more efficient resource management, increased access to financing and promoted financial transparency within the association. In addition, the contribution of this standard to the financial sustainability of the organization was highlighted by providing a clear regulatory framework for the valuation of biological assets and agricultural products, which resulted in greater efficiency in the production and marketing of agricultural products. These findings underscore the importance of IAS 41 in strengthening agricultural accounting for small and medium-sized production associations.